Contactless digital financial innovation and global contagious COVID-19 pandemic in low income countries: Evidence from Uganda - George Okello Candiya Bongomin; Waswa Balunywa; Edith Mwebaza Basalirwa; Muhammed Ngoma; Joseph Mpeera Ntayi (Cogent Economics & Finance, 2023)
Since its outbreak, Covid-19 has led to upsurge in economic inactivity, leaving many households and firms without access to and use of basic services including financial services. Specifically, with the lockdown and curfew, most traditional bank branches remained closed, leaving households without access to quality, affordable, convenient, and safe financial services. This study aims to establish whether contactless digital financial innovation like mobile money can promote access to and use of financial services in the presence of pandemic positive emotions in low-income countries. SmartPLS 3.0 was used to construct the structural equation mediation model with bootstrap based on 2,737 valid responses. It was found that contactless digital financial innovation such as mobile money significantly promotes access to and use of financial services in low-income countries under pandemic situation. Additionally, the findings showed that the use of contactless digital financial innovation promotes Covid-19 standard operating procedures in low-income countries. Cognizant to the role of human behaviour in technology adoption and usage, the structural equation model with bootstrapping revealed a 4 percentage points improvement in Covid-19 standard operating procedures due to the use of contactless mobile money channel. Accordingly, the findings could be useful in the following ways: governments in low-income countries may use it to promote public health concern under pandemic situations. Mobile money can allow individuals to store, send, and receive money during situation of limited or no movements caused by pandemic health restrictions. Besides, the use of contactless digital financial innovation may promote digital commerce in low-income countries under the pandemic situation. Similarly, mobile money can be used to promote government-to-person, person-to-person, person-to-business, and business-to-person payments under emergency situations. The findings may also help governments in low-income countries to rethink about taxes levied on mobile money.
Keywords: 330; Appraisal Tendency Framework; broaden-and-build theory; digital financial innovation; mobile money technology; pandemic mitigation measures; positive emotions; SARS-CoV-2